Teachers' perception of health, remote work, and the students' situation during the COVID-19 pandemic - Aline de Sousa Justino; Osmar de Oliveira Cardoso; Roniele Araújo de Sousa; Mykaelle Soares Lima (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2024)
Objective: To evaluate the teachers' perceptions regarding their emotions, health and work, as well as the students' situation, during the pandemic. Methods: Cross-sectional, quantitative and descriptive study, carried out with teachers from the public education network in the state of Piauí. The bivariate analysis model was applied using Pearson's Chi-square test, considering the significance level at 5% to check associations and to analyze the reliability of the questionnaire. Internal consistency was calculated using Cronbach's alpha coefficient. Results: Hopeless was the emotion most perceived by teachers. Conversely, they felt satisfied with their health and work. There was no influence of sociodemographic characteristics on perceived hopeless. In addition, they stated that they had good expectations when the pandemic was over. Regarding the students' situation, it was identified that they partially agreed that there had been harm. Conclusion: Feeling hopeless during the pandemic was independent of the individual's sociodemographic characteristics, as well as the teacher's gender, age or race/skin color.